Doktrin Manusia dan Dosa - Sarmaul Sarmaul; Yuwantri Yuwantri; Siska Panduwinata; Yuwantri YuwantriRina Lorensa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The Docrtrine of Man and principles discusses the definition of man in the context of the Bible, explaining that man was created by God as a special creature with a body, soul and spirit. There are three views regarding human nature, trichotomy, dichotomy, monochotomy.Sin is defined as a violation of God’s commands, which results in separation. Humans from God and the ongoing negative impacts. Sin has various types and impacts, ranging from God’s judgment to spiritual separation from him.